GABAA Receptor-Modulating Steroids in Relation to Women’s Behavioral Health - Bäckström, Torbjörn; Bixo, Marie; Strömberg, Jessica (Current psychiatry reports, 2015)
In certain women, increased negative mood relates to the progesterone metabolite, allopregnanolone (allo), during the luteal phase of ovulatory menstrual cycles, the premenstrual dysphoric disorder (PMDD). In anovulatory cycles, no symptom or sex steroid increase occurs but symptoms return during progesterone/allo treatment. Allo is a potent GABA A receptor-modulating steroid and as such is expected to be calming and anxiolytic. A relation to negative mood is unexpected. However, this paradoxical effect can be induced by all GABA A receptor modulators in low concentrations whereas higher concentrations are calming. The severity of the mood symptoms relate to allo in an inverted U-shaped curve at endogenous luteal-phase serum concentrations. Allo’s effects on the GABA A receptor can be antagonized by isoallopregnanolone (ISO), an antagonist to allo. ISO has also been used in a preliminary clinical trial on PMDD ameliorating symptoms with good effect in PMDD patients.